2007
DOI: 10.1897/07-039r.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of cytochrome P4501A biomarker measurements in fish

Abstract: Abstract-Induction of the cytochrome P4501A (CYP1A) enzyme system in fish is a common biomarker of exposure to aromatic hydrocarbons. Induction of CYP1A can be measured at a number of steps in the transcription-translation-functional protein pathway using a variety of techniques. The present study examined the range of these measurements from 94 published papers in an attempt to examine the statistical characteristics of each method. Cytochrome P4501A induction, as measured by catalytic ethoxyresorufin-O-deeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 125 publications
(241 reference statements)
1
11
0
Order By: Relevance
“…It has also repeatedly been reported that EROD can substantially be inhibited by elevated levels of PCBs, fluoranthene (a prevalent PAH), dioxins and heavy metals (e.g., Viarengo et al 1997;Gooch et al 1989;Willett et al 2001;Ortiz-Delgado et al 2008). EROD activity is technically easy to measure, and it is still considered as a robust biomarker (Oris and Roberts 2007); however, this enzymatic activity biomarker shows some limitations that can make interpretation sometimes difficult in field studies (Spearow et al 2011). Although several studies have focused separately on Cyp1a induction at different organizational levels such as gene expression (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also repeatedly been reported that EROD can substantially be inhibited by elevated levels of PCBs, fluoranthene (a prevalent PAH), dioxins and heavy metals (e.g., Viarengo et al 1997;Gooch et al 1989;Willett et al 2001;Ortiz-Delgado et al 2008). EROD activity is technically easy to measure, and it is still considered as a robust biomarker (Oris and Roberts 2007); however, this enzymatic activity biomarker shows some limitations that can make interpretation sometimes difficult in field studies (Spearow et al 2011). Although several studies have focused separately on Cyp1a induction at different organizational levels such as gene expression (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P4501A can also be activated by other pathways and plays a strong role in steroid hormone biosynthesis, tryptophan and retinol metabolism (review in Monostory et al 2009). Induction of Cyp1a varies between fish species (Wirgin et al 1996;Willett et al 1997;Oris and Roberts 2007), so that a specific evaluation needs to be performed before using this biomarker on a sentinel species in environmental monitoring programs. In this study, we thus focus on both Cyp1a gene expression and protein content in order to provide a combined biomarker specific for the striped bass Morone saxatilis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 the ratio was 220.0. Thus, all analyses were based on comparisons of EROD values between oiled and reference sampling locations within years [8,14]. This approach accounted for any systematic bias in laboratory procedures between years.…”
Section: Resultsmentioning
confidence: 99%
“…4A, B) [10,28], a much greater and statistically significant difference in EROD activity in harlequin ducks from oiled and unoiled sites is needed to demonstrate exposure to ERODinducing chemicals [57]. By this metric, we conclude that the EROD data for harlequin ducks from oiled and unoiled areas are all within the range of natural variability of background levels and, therefore, do not prove continuing exposure of harlequin ducks in the NKI area to EVOS PAH residues, particularly in the absence of a proven exposure pathway.…”
Section: Indirect Methods For Assessing Exposure To Evosmentioning
confidence: 99%